1999
DOI: 10.1086/307518
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Stellar Evolution with Binary Systems

Abstract: We have compared stellar evolution models with the three intermediate-mass binary systems V2291 Oph, a Aur, and g And, whose masses are determined accurately within 7%. These systems were recently regarded by and coworkers as systems that favor evolution with moderate overshoot mixing Schro der from the convective cores. While they assumed a standard Population I metallicity for these binaries, we have taken into account the available heavy-element abundance data in the literature. We have taken two approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
(19 reference statements)
2
13
0
Order By: Relevance
“…The inferred age is log t = 8.778 −0.012 +0.031 which means that it is not as well determined as the previous case. This should be compared with the models computed by Iwamoto & Saio (1999): these authors found that core overshooting is not necessary to explain the astrophysical parameters of η And if models with subsolar metallicity are adopted; their mixing length parameter is very similar to ours (1.40). The approximately solar composition also requires some changes in the input physics.…”
Section: Stellar Models For η and V2291 Oph And Sz Censupporting
confidence: 61%
See 3 more Smart Citations
“…The inferred age is log t = 8.778 −0.012 +0.031 which means that it is not as well determined as the previous case. This should be compared with the models computed by Iwamoto & Saio (1999): these authors found that core overshooting is not necessary to explain the astrophysical parameters of η And if models with subsolar metallicity are adopted; their mixing length parameter is very similar to ours (1.40). The approximately solar composition also requires some changes in the input physics.…”
Section: Stellar Models For η and V2291 Oph And Sz Censupporting
confidence: 61%
“…The mixinglength parameter was increased to 1.85 and the final solution is better than that by adopting the models with subsolar metallicity since the inferred age is log t = 8.918 −0.020 +0.003 . Comparing our models with Z = 0.018 with those by Iwamoto & Saio (1999) (both adopting core overshooting), the mixing-length parameter is similar, as the core overshooting parameter (α ov = 0.20 and 0.15, respectively).…”
Section: Stellar Models For η and V2291 Oph And Sz Cenmentioning
confidence: 54%
See 2 more Smart Citations
“…Figure 17 shows the adopted stellar lifetime function as a function of initial mass and metallicity, which is provided by Kodama & Arimoto (1997). The stellar evolution tracks are calculated with the code described in Iwamoto & Saio (1999) with the core overshooting. Because of the coarse mass grid, there is a tiny irregularity at 1.8M ⊙ (Z = 0.004, 0.008), 2.0M ⊙ (Z = 0.02), 2.2M ⊙ (Z = 0.0001-0.002), and 3.3M ⊙ (Z = 0.0002) in the table, which we have smoothed with interpolation.…”
Section: Sn Ia Formulationmentioning
confidence: 99%